2021
DOI: 10.2903/j.efsa.2021.6884
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of thaumatin (E 957) as food additive

Abstract: The present opinion deals with the re-evaluation of thaumatin (E 957) when used as a food additive. Thaumatin is a natural plant protein, consisting of thaumatin I and thaumatin II proteins together with minor amounts of plant constituents, obtained by acidic aqueous extraction of the arils of the fruit of Thaumatococcus daniellii plant. The Panel followed the conceptual framework for the risk assessment of certain food additives and considered that thaumatin is a digestible protein; adequate exposure estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The NOAEL identified from the above‐mentioned subchronic toxicity study in dogs was confirmed to be 1,305 mg/kg bw per day in male dogs and 1,476 mg/kg bw per day in female dogs. Among all NOAELs identified in different toxicological studies, all corresponding to the highest dose tested, the FAF Panel used the highest NOAEL of 5,200 mg/kg bw per day (the highest dose tested in males), identified in a subchronic toxicity study with rats (Ben‐Dyke et al., 1976 , as cited by EFSA FAF Panel, 2021 ), to calculate the Margin of Safety (MOS) for humans. In addition, the FAF Panel concluded that thaumatin does not raise concern for genotoxicity and developmental toxicity.…”
Section: Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The NOAEL identified from the above‐mentioned subchronic toxicity study in dogs was confirmed to be 1,305 mg/kg bw per day in male dogs and 1,476 mg/kg bw per day in female dogs. Among all NOAELs identified in different toxicological studies, all corresponding to the highest dose tested, the FAF Panel used the highest NOAEL of 5,200 mg/kg bw per day (the highest dose tested in males), identified in a subchronic toxicity study with rats (Ben‐Dyke et al., 1976 , as cited by EFSA FAF Panel, 2021 ), to calculate the Margin of Safety (MOS) for humans. In addition, the FAF Panel concluded that thaumatin does not raise concern for genotoxicity and developmental toxicity.…”
Section: Assessmentmentioning
confidence: 99%
“…In their opinions, the EFSA ANS Panel (EFSA ANS Panel, 2015 ) and the EFSA FAF Panel (EFSA FAF Panel, 2021 ) recalculated the NOAEL, from the same subchronic toxicity study in dogs, which resulted in values of 1,305 mg/kg bw per day in male dogs and 1,476 mg/kg bw per day in female dogs. These NOAELs are the lowest among all NOAELs (all corresponding to the highest dose tested) identified by the EFSA FAF Panel from the available toxicological studies.…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations